The Risky Closed Economy: A Holistic, Longitudinal Approach to Studying Fear and Anxiety in Rodents - Schuessler, Bryan P.; Zambetti, Peter R.; Fukuoka, Kisho M.; Kim, Eun Joo; Kim, Jeansok J. (Frontiers in Behavioral Neuroscience, 2020)
Basic research of fear and anxiety in rodents has historically utilized a limited set of behavioral paradigms, for example, Pavlovian (classical) fear conditioning, the elevated plus maze, or inhibitory (passive) avoidance. These traditional paradigms measure a limited selection of variables over a short duration, providing only a “snapshot” of fear and anxiety-related behavior. Overreliance on these paradigms and such behavioral snapshots ultimately leads to a narrow understanding of these complex motivational states. Here, we elaborate on the closed economy; a seldom used paradigm that has been modified to comprehensively study fear and anxiety-related behavior and neurocircuitry in rodents. In this modified “Risky Closed Economy” paradigm, animals live nearly uninterrupted in behavioral chambers where the need to acquire food and water and avoid threat is integrated into the task. Briefly, animals are free to acquire all of their food and water in a designated foraging zone. An unsignaled, unpredictable threat (footshock) is introduced into the foraging zone after a baseline activity and consumption period to model the risk of predation, which is then removed for a final extinction assessment. This longitudinal design, wherein data from a multitude of variables are collected automatically and continuously for 23 hrs/day over several weeks to months, affords a more holistic understanding of the effects of fear and anxiety on day-to-day behavior. In addition, we discuss its general benefits relevant to other topics in neuroscience research, its limitations and present data demonstrating for the first time The Risky Closed Economy’s viability in mice.